PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SDN 1 WAY DADI SUKARAME BANDAR LAMPUNG - Ramania, Yulisa (UNISAN JURNAL, 2024)
This study aims to carry out the supervision of the principal in improving the performance of SDN 1 way dadi Sukarame teachers. This study uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. This participatory observation technique was carried out to observe the geographic location in the form of a location plan and environmental conditions, the school’s vision, mission, strategy and motto as well as the condition of human resources at SDN 1 way dadi Sukarame. Based on the results of the description that has been described that during the implementation of supervision, the attitude of the school principal did not interfere with the course of the learning process of Islamic religious education in class and even the principal at the end of the lesson provided motivation to students to continue studying diligently. In the follow-up stage, the supervision results are discussed jointly between the Islamic religious education teacher and the school principal, namely discussing the teacher’s shortcomings in teaching with the hope that in the future the teacher can improve it.